Private and public lies : the discourse of despotism and deceit in the Graeco-Roman world - Turner, Andrew J.; Chong-Gossard, K. O.; Vervaet, Frederik. (Impact of Empire, 2010)
Graeco-Roman literary works, historiography, and even the reporting of rumours were couched as if they came in response to an insatiable desire by ordinary citizens to know everything about the lives of their leaders, and to hold them to account, at some level, for their abuse of constitutional powers for personal ends. Ancient writers were equally fascinated with how these same individuals used deceit as a powerful tool to disguise private and public reality. The chapters in this collection examine the themes of despotism and deceit from both historical and literary perspectives, over a range of historical periods including classical Athens, the Hellenistic kingdoms, late republican and early imperial Rome, late antiquity, and Byzantium.